Effect of Copper Source on Finishing Pig Growth Performance and Carcass Characteristics - Samantha A. Swanson; Jordan T. Gebhardt; Jason C. Woodworth; Mike D. Tokach; Joel M. DeRouchey; Robert D. Goodband; Katelyn N. Gaffield; Matt Einarson (Kansas Agricultural Experiment Station Research Reports, 2025)
A total of 2,160 pigs (PIC 337 × 1050; initially 53.1 ± 1.31 lb) were used in a 113-day study with 27 pigs per pen and 20 replications per treatment across two barns. Pens of pigs were blocked by weight and randomly allotted to one of four dietary treatments: a control diet containing a base level of Cu, or a pharmacological level of one of three sources, tribasic copper chloride (TBCC) source 1 (TBCC, 58%, SAM Nutrition, Bloomington, MN), TBCC source 2 (Intellibond C, 54%, Selko, Tilburg, Netherlands), or CuSO4. All diets contained a base level of CuSO4 provided by the trace mineral premix contributing 16 mg/kg Cu in phases 1 and 2, 13 mg/kg Cu in phase 3, and 11 mg/kg Cu in phase 4. An additional 150 mg/kg Cu was added from each specific source. Treatment diets were formulated in four phases from approximately 50 to 110 lb, 110 to 165 lb, 165 to 220 lb, and 220 lb to marketing (approximately 280 lb). Mortality and removals were recorded for the duration of the trial, and economics were calculated. In the grower period (d 0 to 56), pigs fed pharmacological levels of Cu had greater (P < 0.001) ADG and BW compared to pigs fed the base Cu level. No evidence of a difference was observed between Cu sources when fed at pharmacological levels. A tendency (P ≤ 0.059) for increased ADFI and improved F/G was observed in pigs fed pharmacological levels of Cu compared to the base level. In the finishing period (d 56 to trial end), there was no evidence of any differences in ADG, ADFI, or F/G between treatments. Overall, pigs fed pharmacological levels of Cu had greater (P = 0.018) ADG and a tendency for a greater (P = 0.072) ADFI than pigs fed the base level of Cu. Hot carcass weight was greater (P = 0.031) in pigs fed pharmacological levels of Cu than in pigs fed the base level of Cu. No evidence of differences was found for other carcass characteristics or removals and mortality. There was a tendency (P = 0.083) for pigs fed pharmacological levels of Cu to have higher feed cost per lb/gain than pigs that were fed basal levels of Cu. However, it did not impact IOFC, and no other differences in economic criteria were observed. These data suggest that feeding pharmacological levels of Cu improves growth performance, with the largest benefit observed during the grower period; however, there were no differences between Cu sources when fed at pharmacological levels.
Keywords: finishing pigs; tribasic copper chloride; copper sulfate